If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5x = 10 + x Solving 3 + -5x = 10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -5x + -1x = 10 + x + -1x Combine like terms: -5x + -1x = -6x 3 + -6x = 10 + x + -1x Combine like terms: x + -1x = 0 3 + -6x = 10 + 0 3 + -6x = 10 Add '-3' to each side of the equation. 3 + -3 + -6x = 10 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = 10 + -3 -6x = 10 + -3 Combine like terms: 10 + -3 = 7 -6x = 7 Divide each side by '-6'. x = -1.166666667 Simplifying x = -1.166666667
| 4(-6)+10=2(n-7)-6 | | -11-7b=-7(b+2) | | -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 | | 351=3b | | 0.19y+0.05(y+7000)=2030 | | 3(-7a+6)-6a=-2a+18 | | Ax+r=5 | | 325-m=1500+2(m-500) | | 11x+8-30-x=-2(2x+4)-3(2x-2) | | 9y-3=19-24 | | -134=5(1+3x)-4 | | a+x=y+z | | 10-2.7y=y | | 3x-5(x-2)=-6+4x+4 | | 2x^5-6x^4-216x^3=0 | | -2(5x-4)=22 | | x-13=23-2x | | -3(x-2)-1=5(x+3)+38 | | g(x)=-2x+5 | | 5.9x-4.9x^2=0 | | 9+(9+.5x)=x | | 11+7q=15+6q | | -(2x-5)=12 | | -(n-4)+3(n-2)=2 | | y^2+25=1oy |